ANALISIS PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GURU DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA SMP NEGERI DI KECAMATAN BLANG MANGAT - Nurmalawati Nurmalawati; Jullimursyida Jullimursyida; Mohd Heikal (Universitas Malikussaleh, 2022)
This study aims to determine the effect of work environment and work discipline on teacher performance and motivation. In addition, it also aims to see the role of motivation as a mediation between these relationships. The data used in this study is primary data by distributing questionnaires, while the sampling technique is census. So the sample in this study amounted to 120 respondents at the State Junior High School in the District of Blang Mangat. The analytical method in this study is quantitative and the data analysis technique uses Structural Equation Model (SEM) analysis which is operated through SEM Amos. The results of the study found that the work environment had no effect on motivation, while work discipline had a positive and significant effect on motivation. The work environment and motivation have a positive and significant effect on teacher performance, but work discipline has a negative and significant effect on teacher performance. In addition, work motivation is not able to mediate the relationship between the work environment and teacher performance, but motivation fully mediates the relationship between work discipline and teacher performance